2012
DOI: 10.1038/emboj.2012.171
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and thermal stimuli control K2P2.1 (TREK-1) through modular sensory and gating domains

Abstract: Metabolic and thermal stimuli control K2P2.1 (TREK-1) through modular sensory and gating domainsThe two-pore domain potassium channel K2P2.1 (TREK-1) responds to extracellular and intracellular stimuli, including pH and temperature. This study elucidates how the intracellular sensor element relays metabolic and thermal stimuli to the extracellular C-type gating element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
180
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(194 citation statements)
references
References 74 publications
14
180
0
Order By: Relevance
“…The mutations seen in this study in the TM4 region of TASK3 (A237T, G236R) might be anticipated to interfere with gating of the channel by altering movement of this TM4 region. This could result in either an interaction with the bundle-crossing region of the channel that is in close proximity to this region or, perhaps more likely, interference with transduction of the regulatory signal from the intracellular regulatory components to the gating region at the selectivity filter via TM4, as seen for TREK1 channels (Bagriantsev et al, 2011(Bagriantsev et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations seen in this study in the TM4 region of TASK3 (A237T, G236R) might be anticipated to interfere with gating of the channel by altering movement of this TM4 region. This could result in either an interaction with the bundle-crossing region of the channel that is in close proximity to this region or, perhaps more likely, interference with transduction of the regulatory signal from the intracellular regulatory components to the gating region at the selectivity filter via TM4, as seen for TREK1 channels (Bagriantsev et al, 2011(Bagriantsev et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the TM4 region of K2P channels has been suggested to be crucial in transducing gating signals from the cytoplasmic side of the channel to the selectivity filter gate (Bagriantsev et al, 2011(Bagriantsev et al, , 2012Piechotta et al, 2011), so we determined whether mutations of amino acids in this region interfered with gating and regulation of TASK3 channels.…”
Section: Recovery Of Current In Mutated Task3 Channelsmentioning
confidence: 99%
“…More recently, this strategy was applied to the study of TREK-1 potassium channel, which is highly temperature-sensitive like TRPV1 27 . Introducing an unstructured triple-glycine peptide between the M4 segment and the C terminus was found to eliminate high temperature-sensitivity, supporting the idea that the C-terminus of TREK-1 is responsible for sensing temperature change 28 . In these studies, insertion of a short, unstructured peptide was used to perturb coupling between…”
mentioning
confidence: 63%
“…These sensors can be partially disengaged from the gating machinery by weakening the connection between the C terminus and TM4. This is accomplished by introducing a treble glycine or alanine replacement at the end of TM4, mutations that presumably impair the C terminus-TM4-SF coupling (Bagriantsev et al, 2012). The idea for C terminus and SF coupling was already present in the work of Zilberberg et al (2000Zilberberg et al ( , 2001, which showed that C terminus phosphorylation affected C-type inactivation gating in KCNK0 channel.…”
Section: An All-encompassing Role For the Selectivitymentioning
confidence: 99%
“…No evidence for differences in the SF or the pore helices between these putative activation states has been found, however. In the TRAAK study (Lolicato et al, 2014), gain-offunction mutant channel structures that had previously been functionally characterized (Bagriantsev et al, 2012) were used to probe the C terminus-TM4-SF coupling hypothesis of gating. In contrast to what has been described here, the structures revealed a situation in which the down conformation was conductive, and the up conformation corresponded to the closed channel; this discordant finding of Lolicato et al (2014) remains unexplained.…”
Section: A Novel Hypothesis To Explain Traak Mechanosensitivitymentioning
confidence: 99%